A Case of Inappropriate Antidiuretic Hormone Secretion Syndrome Associated With COVID-19 Pneumonia Treated With Boluses of Hypertonic Saline for Reversal of Symptomatic Hyponatremia - Miranda, Gonzalo Francisco (J Endocr Soc, 2021)
Hyponatremia is the most common electrolyte disorder, which can occur in outpatients and hospitalized patients, so both first-contact doctors and specialists must keep up-to-date on the prevention, recognition, diagnosis and management of this complication. A 68-year-old male patient presents to Dos de Mayo National Hospital Emergency Department. He was diagnosed as COVID-19 pneumonia and hospitalized for management of acute respiratory failure. The patient had neurological impairment associated with poor oral tolerance. Initial laboratory examinations were C-reactive protein in 363.5 mg/L, serum sodium of 128.42 mmol/L and urine sodium was 83 meq/L. Osmolality in plasma was 266.15 mOsm/Kg and urine osmolality was 420 mOsm/Kg. Thyroid function tests as well as cortisol levels were in normal range. Our patient was diagnosed as SIAD by hyponatremia, osmolality in plasma <275 mOsm / kg, urine osmolality > 100 mOsm / kg, urine sodium > 40 mEq / l, euvolemic state and exclusion of cortisol and thyroid hormone deficiency. Treatment of hyponatremia was initiated and rapidly elevate plasma sodium by 4 meq/l in the first 6 hours. There was clinical improvement. Blood sodium levels ranged from 115 to 135 mmol/L with bolus therapy of hypertonic solutions in 72 hours. Intravenous boluses of hypertonic saline should be administered to rapidly elevate plasma sodium by 4 to 6 mEq/L in the first 6 hours. The data shows that fluid bolus therapy is more effective in acutely elevating plasma sodium than traditional low-dose hypertonic saline infusion that may lead to avoidable deaths according to recent guidelines. In this case a strategy based with bolus therapy for reversal of hyponatremia was used effectively. A number of cases of COVID-19 pneumonia are associated with SIAD. The presence of SIAD could be a clue to diagnosing COVID-19. SIAD is a major complication of COVID-19 and could be the first and only manifestation. In cases of SIAD without a clear etiology we should suspect COVID-19 in a patient with respiratory distress in the current pandemic. Syndrome of inappropiate antidiuresis (SIAD) should be assessed in every patient with COVID-19 as their treatment and early identification decreases mortality. The association between COVID-19 pneumonia and SIAD should be further identified, requiring doctors to be aware of this condition. Additional studies are required to determine the incidence and pathogenesis of SIAD in patients with COVID-19.